Critical combinations of shear and direct axial stress for curved rectangular panels - Schildcrout, Murry (National Advisory Committee for Aeronautics, 1949)
A solution is presented for the problem of the buckling of curved rectangular panels subjected to combinded shear and direct axial stress. Charts giving theoretical critical combinations of shear and direct axial stress are presented for panels having five different length-width ratios.
"August 1949."
NACA TN No. 1928.
Keywords: Plates (Engineering); Curvature.; Buckling (Mechanics); Shear (Mechanics); Strains and stresses.; elektronické knihy; electronic books